Zooplankton Community Structure in Seagrass Ecosystem, Tongkaina Village, Bunaken Darat District, Manado City - Brenda V.A. Lahiwu; Rose O.S.E. Mantiri; Ferdinand F. Tilaar; Laurentius Th. X. Lalamentik; Ruddy D. Moningkey; Billy T. Wagey (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2021)
This study aims to determine the type and community structure of zooplankton in the Tongkaina seagrass aquatic ecosystem. Sampling was carried out at 3 location points using plankton nets. Plankton net was drawn along 50 meters from the sea towards the beach. There are 14 genera of zooplankton in the morning and 17 genera in the afternoon. The total density of zooplankton in the morning was 0.064 individual/l , and in the afternoon 0.114 individual/l. The highest density of zooplankton in the morning is Limacina and in the afternoon, Calanus. The zooplankton Diversity Index (H ') in the morning is 2.5907 and in the afternoon is 2.7321, indicating that the diversity level is less diverse. Morning uniformity (e) zooplankton index was 0.5614 and in the afternoon 0.5267, showed that the distribution pattern of zooplankton was moderate. The zooplankton dominance (C) index in the morning was 0.0783 and in the afternoon 0.0720. This shows that there is no dominant genus. Water conditions fall into the good category due to the temperature, salinity, and pH that are quite stable and are still within the limits of feasibility for zooplankton life.    Keywords: Zooplankton, Community Structure, Seagrass, Tongkaina Waters.Keywords: Zooplankton, Community Structure, Seagrass, Tongkaina Waters  ABSTRAKPenelitian ini bertujuan untuk mengetahui jenis dan struktur komunitas zooplankton yang ada di ekosistem perairan lamun Tongkaina. Pengambilan sampel dilakukan pada 3 titik lokasi dengan menggunakan jaring plankton.Plankton net ditarik sepanjang 50 meter dari laut ke arah pantai. Terdapat 14 genus zooplankton pada waktu pagi dan 17 genus pada waktu sore. Kepadatan total zooplankton pada waktu pagi hari 0.064 ind/l dan sore hari 0.114 ind/l. Kepadatan relatif zooplankton yang tertinggi pada pagi hari yaitu Limacina dan pada sore hari yaitu Calanus. Adapun Indeks Keanekaragaman (H’) zooplankton pada pagi hari sebesar 2.5907 dan sore hari sebesar 2.7321, menunjukkan bahwa tingkat keanekaragaman kurang beragam. Indeks Keseragaman (e) zooplankton pada pagi hari sebesar 0.5614 dan pada sore hari 0.5267, menunjukkan bahwa pola sebaran zooplankton sedang. Indeks Dominansi (C) zooplankton pada waktu pagi hari sebesar 0.0783 dan sore hari 0.0720. Hal ini menunjukkan bahwa tidak ada genus yang dominan. Kondisi perairan masuk dalam kategori baik dikarenakan suhu, salinitas dan pH cukup stabil dan masih berada dalam batas kelayakan bagi kehidupan zooplankton.Kata kunci: Zooplankton, Struktur Komunitas, Lamun,  Perairan Tongkaina.